(untitled) (Italian Journal of Public Health, 2005)
The paper discusses the role of institutional communication in the case of health risks and emergencies. The article is divided in three sections. The first section examines the most recent theories on risk and on its communicational aspect; the second analyses a recent state of emergency crisis, specifically the panic which stemmed from the perceived danger of an avian flu pandemic in Italy; and finally an example of best practice in the form of a food safety handbook designed and edited by the Italian Ministry of Rural Affairs, which was based on the skills and knowledge acquired during the avian flu emergency.